Last passenger [videorecording (Blu-Ray)] - Nooshin, Omid; Winfield, Zack; Goldberg, Iddo, 1975-; Schofield, David, 1951-; Duncan, Lindsay; Scott, Dougray, 1965-; Tointon, Kara; Yoshizaki, Ado; Bates, Liam; Love, Andy (Umbrella Entertainment [distributor], 2012)
"Overworked doctor and devoted single dad Lewis Shaler (Dougray Scott) is heading home on the last train from London with his young son Max for the Christmas holidays. Unexpectedly the train speeds through one station and then another, with flashing level crossings a fleeting blur. Discovering that the brakes have been sabotaged by a vengeful sociopath determined to cause widespread havoc, Lewis, Max and the remaining passengers face the ultimate challenge of survival. A suspense-filled trip in the tradition of Runaway Train, Unstoppable and Speed, Last Passenger is a track-hugging thrill-ride through a cavernous night of twists, turns and explosive action"--Container.